2021
DOI: 10.7717/peerj.11343
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential genes in upper tract urothelial carcinoma using next-generation sequencing with bioinformatics and in vitro analyses

Abstract: Background We aimed to identify prognostic biomarkers of upper tract urothelial carcinomas (UTUCs), including microRNAs (miRNAs) and genes which account for only 5% to 10% of all urothelial carcinomas (UCs). In Taiwan, this figure is markedly higher, where it can reach up to 30% of UC cases. Materials and Methods Using next-generation sequencing (NGS), we analyzed two pairs of renal pelvis tumors and adjacent normal urothelial tissues to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…We observed PDE5A overexpression in PTC tissues, which is consistent with earlier observations. However, PDE5A is downregulated in other tumor types like upper tract urothelial carcinoma [27] and melanoma [28]. Interestingly, Nagel et al reported that PDE5A has an anti-apoptotic function by reducing the level of cGMP in the cytoplasm, suggesting that PDE5A is an oncogene in Hodgkin's lymphoma [29].…”
Section: Discussionmentioning
confidence: 99%
“…We observed PDE5A overexpression in PTC tissues, which is consistent with earlier observations. However, PDE5A is downregulated in other tumor types like upper tract urothelial carcinoma [27] and melanoma [28]. Interestingly, Nagel et al reported that PDE5A has an anti-apoptotic function by reducing the level of cGMP in the cytoplasm, suggesting that PDE5A is an oncogene in Hodgkin's lymphoma [29].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they found that some tyrosine kinases may be potential treatment strategies. Lee et al and Chen et al used an RNA sequencing approach to distinguish normal/tumor pairs in patients with urothelial cancer (GSE159824 and GSE133624) [ 122 , 123 ]. Many scientists have generated their data from patient-derived xenografts (PDXs) and organoids (GSE155007 and GSE134292) [ 124 ].…”
Section: Omics Datasets Available In Ucmentioning
confidence: 99%